The effect of horizontal pay dispersion on the effectiveness of performance-based incentives - Grabner, Isabella; Martin, Melissa A. (Accounting, Organizations and Society, 2021)
In response to general calls for increased transparency in society, pay transparency policies are growing in importance. Given that pay transparency unavoidably gives employees the opportunity to make comparisons between themselves and others, in this study we address the question of how these comparisons impact the incentive effects of performance contingent pay, and consequently their performance outcomes. Specifically, we empirically examine whether horizontal pay dispersion alters the effectiveness of performance-based pay contracts, which firms typically use to incentivize effort. Exploiting our unique access to a large healthcare provider, we document the moderating role of horizontal pay dispersion on the effectiveness of individual monetary incentives at generating increased individual performance. To provide a more nuanced understanding of the moderating effect of pay dispersion, we further examine the boundary conditions of the proposed interaction. In particular, we examine the differential effect of overall pay dispersion on employees that rank high versus low in the pay distribution and disaggregate overall pay dispersion into performance-related versus performance-unrelated pay dispersion. Our findings consistently show a positive moderating effect of pay dispersion when employees are more likely to consider the observed pay dispersion as legitimate, and a negative moderation effect when this is less likely the case. Our study strengthens the understanding of how individual level incentives function in the context of a multi-person firm setting. Our results document that individual incentives are effective, but also suggest that pay dispersion can have a significant influence on the incentive-performance relation. These findings provide some evidence that individuals are concerned not only with their own payout, but also with that of others, and that this concern has a significant impact on individual’s effort provision, and consequently performance.